Determine the Area and Distribution urban in the western part of the AL sweeda, using remote sensing techniques (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Optimum Index Factor (OIF) technique of statical analysis is fusion with Decision Tree Classification (DTC) method in determine the spectral critical value for separation the features in the image processing programs, and the architecture of this approach is designed for accuracy extracting the area and distribution urban from space image. Accuracy assessment of that approach is tested by comparing the supervised classification results for these feature from both the original bands of image and synthetical bands/indices of the image upon OIF value. Applied results of the approach on certain district represent the north Swaidaa city by Quick Bird image are: 98% for the suggested approach opposite 93% for supervised classification method of the synthetical bands image and 82% for original bands image. Accuracy of the approach is derived from exact separation the urban feature than similar spectrally objects in the image as basalt exposures and roads, where achievement of the other processing methods are less.